2007
DOI: 10.1209/0295-5075/78/56001
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium critical dynamics with domain interface

Abstract: With Monte Carlo simulations, we investigate the relaxation dynamics with a domain wall for magnetic systems at the critical temperature. The dynamic scaling behavior is carefully analyzed, and a dynamic roughening process is observed. For comparison, similar analysis is applied to the relaxation dynamics with a free or disordered surface.In the past years, much effort of physicists has been devoted to the understanding of nonequilibrium dynamic processes. Phase ordering dynamics, spin glass dynamics, structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…1. We find that similar to the classical case, [22,23] as the time evolves, the sharp domain wall will blur and expand into an interfacial region. Let us focus on the behavior of the local parameter at the position 𝑥, with 𝑥 denoting the distance to the initial domain wall.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…1. We find that similar to the classical case, [22,23] as the time evolves, the sharp domain wall will blur and expand into an interfacial region. Let us focus on the behavior of the local parameter at the position 𝑥, with 𝑥 denoting the distance to the initial domain wall.…”
mentioning
confidence: 53%
“…[21] In particular, critical relaxation dynamics with a domain interface in a semi-ordered initial state was studied. [22,23] Those works showed that different from the relaxation dynamics with a homogeneous initial state, the initial domain wall can expand into a growing interfacial region, and in this region the order parameter decays obeying a distinct scaling relation 𝑀 ∝ 𝑡 −𝛽 1 /𝜈𝑧 with 𝛽1 being an additional dynamic exponent. In quantum sys-tems, exotic prethermal dynamics induced by the interface in the 2D quantum Ising model was discovered.…”
mentioning
confidence: 99%
“…As time evolves, the domain wall moves and roughens, while the bulk remains unchanged. Therefore, the domain wall can also be called a domain interface [46,47]. Main results of numerical simulations are presented with the lattice size L x = 25 and L y = 512, up to t max = 400 000 Monte Carlo steps (MCS).…”
Section: Model and Scaling Analysismentioning
confidence: 99%
“…Recent activities include various applications and developments such as theoretical and numerical studies of the Josephson junction arrays and aging phenomena [45][46][47][48][49]. A kind of domain-wall roughening process at order-disorder phase transitions has also been revealed [50][51][52]. Very recently, the short-time behavior of the domain-wall relaxation around the depinning transition is noted in simulations and experiments [14,15,53].…”
Section: Introductionmentioning
confidence: 99%